Diseño de un modelo de gestión de mantenimiento para el departamento de Ingeniería del hotel San José Costa Rica Marriott - Monge-Martínez, Harold-Yamil (Instituto Tecnológico de Costa Rica, 2017)
The Engineering in Marriott Hotels, at the present, is matter to innovate and to the continuous improvement in the processes. While working under the pressure of reducing costs, adding value and solving the needs of the guests. The main objective of the Engineering Department is to operate and maintain the infrastructure, facilities, equipment, as well as the hotel's furniture in an optimal condition through efficient management, energy and water consumption monitors, guaranteeing enjoyment and customer safety. The project arises as a response to the constant search for improvement. Therefore, the purpose is to find and solve needs that present the maintenance in the hotel. In this way, a diagnosis of the current maintenance situation is made, based on the Covenin 2500-93 standard. Once the weak points are identified, a criticality analysis is carried out, in order to identify the most significant equipment for the operation. Once this is done, an analysis of the equipment is made. For this reason, it is necessary to identify what causes such criticality. A thorough and thorough analysis of the equipment is made in order to solve their needs and take them to a more adequate operational context. Also, a Balanced Scored Card was designed, in order to monitor progress in the department. The costs incurred by Engineering, were calculated if the management model is implemented. Finally, some of the measures for its immediate implementation are discussed, thanks to the good disposition of the Engineering Department.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Gestión; Diagnóstico; Balanced Scored Card; Mantenimiento; Monitoreo; Research Subject Categories::TECHNOLOGY::Engineering mechanics